2018
DOI: 10.3390/nu10091267
|View full text |Cite
|
Sign up to set email alerts
|

The Gut-Brain Axis in Alzheimer’s Disease and Omega-3. A Critical Overview of Clinical Trials

Abstract: Despite intensive study, neurodegenerative diseases remain insufficiently understood, precluding rational design of therapeutic interventions that can reverse or even arrest the progressive loss of neurological function. In the last decade, several theories investigating the causes of neurodegenerative diseases have been formulated and a condition or risk factor that can contribute is described by the gut-brain axis hypothesis: stress, unbalanced diet, and drugs impact altering microbiota composition which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 103 publications
(128 reference statements)
0
44
0
4
Order By: Relevance
“…Pre-and probiotics have demonstrated the ability to manipulate gut microbiota and to influence the circulating levels of LPS [19]. However, we did not intend to review all potential and nutritional factors that might increase levels of LPS and prefer to limit our hypothesis to lipids, which is a well-known risk factor for AD [77].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-and probiotics have demonstrated the ability to manipulate gut microbiota and to influence the circulating levels of LPS [19]. However, we did not intend to review all potential and nutritional factors that might increase levels of LPS and prefer to limit our hypothesis to lipids, which is a well-known risk factor for AD [77].…”
Section: Discussionmentioning
confidence: 99%
“…Bi-directional interactions with microbiota and peripheral metabolism add another layer of complexity to the metabolomic status. For instance, polyphenols and ω-3 PUFAs may be beneficial to neurons through the stimulation of a healthy GM, which may further enhance their effect by generating nutrient-derived metabolites [ 377 , 378 ]. Meng et al used systemic nutrigenomics to elucidate how ω-3 PUFAs counteract the harmful effects of fructose in brain rats [ 379 ], providing rational support for targeted dietary interventions in humans.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…If the interaction between nutrients (micro and macro) and microbiota is very tight, such a relation essentially concerns polyphenols [312]. Polyphenols are a large family of natural compounds produced by plants endowed with scavenging protective properties against the oxidative stress and/or inflammatory signaling occurring in the brain during neurodegeneration.…”
Section: Polyphenolsmentioning
confidence: 99%
“…As known (see above, Section 2.1), the bioavailability of this group of compounds is poor-due to low absorption and fast metabolism leading to their rapid elimination from the organism-however, gut microbiota metabolizes them into active and bioavailable metabolites. This is an interesting aspect of the issue; in fact, it is suggested that the composition of bacteria is a key element in the response to polyphenol treatment and that gut microbiota are probably responsible for polyphenols health effects by regulating their bioavailability [312].…”
Section: Polyphenolsmentioning
confidence: 99%